2022
DOI: 10.1093/rap/rkac053
|View full text |Cite
|
Sign up to set email alerts
|

Elevated highly sensitive C-reactive protein in fibromyalgia associates with symptom severity

Abstract: OBJECTIVES Fibromyalgia, a common pain syndrome, is thought to be a non-inflammatory, nociplastic condition but evidence implicating neuroinflammation has been increasing. Systemic inflammation may be associated with more severe symptoms in some fibromyalgia patients. We studied healthy controls and fibromyalgia patients with and without systemic inflammation detectable using high-sensitivity C-reactive protein (hsCRP) measurement. METHODS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 52 publications
(67 reference statements)
0
7
0
Order By: Relevance
“…The study design and data acquisition have previously been described in detail 9–12 . In brief, the study cohort comprised 54 female patients with fibromyalgia, aged 18–65 years, from Helsinki University Hospital outpatient clinics, City of Vantaa primary health care, and the private clinic of one of the authors (R.M.).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study design and data acquisition have previously been described in detail 9–12 . In brief, the study cohort comprised 54 female patients with fibromyalgia, aged 18–65 years, from Helsinki University Hospital outpatient clinics, City of Vantaa primary health care, and the private clinic of one of the authors (R.M.).…”
Section: Methodsmentioning
confidence: 99%
“…The study design and data acquisition have previously been described in detail. 9 , 10 , 11 , 12 In brief, the study cohort comprised 54 female patients with fibromyalgia, aged 18–65 years, from Helsinki University Hospital outpatient clinics, City of Vantaa primary health care, and the private clinic of one of the authors (R.M.). Thirty‐one age‐matched female controls were recruited from the staff of these health care units and a local home economics organization (Uudenmaan Martat ry).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its association with elevated CRP (mean approx. 6 mg/L) may be attributed to weight and other comorbidities, and indeed, another study discussed that some patients with this condition show higher serum hsCRP titers, mostly due to being overweight and physical inactive [ 475 , 476 , 477 ]. Overweight but also underweight individuals with Duchenne muscular dystrophy have been reported for increased CRP levels [ 478 ].…”
Section: Current Evidence On C-reactive Protein and Potential Conditionsmentioning
confidence: 99%
“…A study conducted on patients with LBP revealed the variability of the organization of the primary motor cortex, concluding that this difference is the origin of NcplP in this condition [ 31 , 32 ]. The level of C-reactive protein can also be associated with NcplP, as shown in a study conducted on patients with fibromyalgia in which a correlation between the C-reactive protein level and severity of pain was reported [ 33 ].…”
Section: Pathophysiologymentioning
confidence: 99%